Vibration analysis of thick composite sandwich cantilever plates with different core materials - Liu C.W.; Kam Taiyan (ITM Web of Conferences)
Because of their light-weight and high stiffness, composite sandwich cantilever plates have been widely used in different industries. In this paper, a method formulated on the basis of the Ritz method and a simple first-order shear deformation theory (SFSDT) is presented to analyze the free vibration of thin and thick rectangular composite sandwich cantilever plates for determining their modal characteristics. In the Ritz method, two independent sets of characteristic functions, namely, polynomials and trigonometric functions, which satisfy the displacement and force conditions at the fixed edge, have been used to construct the eigenvalue problem for extracting the modal characteristics of the plates. For illustration, some existing theoretical and experimental natural frequencies of composite sandwich plates with different core materials have been used to demonstrate the capability of the proposed method in predicting the actual natural frequencies of thin and thick composite sandwich plates.